Preparation method and application of double-layer film system material with self-erasable surface microstructure

By constructing a thermally crosslinkable polydimethylsiloxane bilayer film system on the polymer surface, ultraviolet exposure triggers a radical reaction to form a self-erase surface microstructure, solving the high cost and complexity problems of traditional methods. It realizes rapid construction and optical performance regulation of polymer surface microstructures, and is suitable for the field of optical encryption.

CN119219961APending Publication Date: 2024-12-31GUANGDONG UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411501901.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The prior art has problems such as high cost, complex processes and difficulty in mass production in the microstructure of polymer surfaces, especially traditional spin coating and photolithography methods require high surface roughness and wettability of substrate materials. Moreover, the low surface energy of traditional polydimethylsiloxane materials leads to low adhesion.

Method used

Using heat-crosslinkable polydimethylsiloxane as the substrate, doped with carbonyl-containing photoinitiator, triggering a radical reaction through ultraviolet exposure, and forming a bilayer film system in the polymerized α-olefin monomer solution. Realize the construction and self-erase of surface microstructures.

Benefits of technology

It realizes a low-cost and simple preparation process of polymer surface microstructure, improves the optical transmittance and surface energy of the material, enhances adhesion, is suitable for the field of optical encryption, and has the feasibility of large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219961A_ABST
    Figure CN119219961A_ABST
Patent Text Reader

Abstract

The invention relates to the field of high polymer materials, in particular to a preparation method and application of a double-layer film system material with a self-erasable surface microstructure, and the preparation method comprises the following steps: preparing an elastomer doped with a carbonyl-containing photoinitiator by taking thermally-crosslinkable polydimethylsiloxane as a base material; the method comprises the following steps: dissolving a polymerizable alpha-olefin monomer in an organic solvent to obtain a corresponding monomer solution; the method comprises the following steps: soaking an elastomer serving as a substrate in a monomer solution, and initiating a free radical reaction by utilizing ultraviolet exposure to generate a surface microstructure on the surface of the elastomer, thereby obtaining the double-layer film system material with the self-erasable surface microstructure. Some surface microstructures with uniqueness and practicability can be formed on the surface of the elastomer obtained after photochemical reaction, the defects of a traditional processing method are overcome, rapid construction of the polymer surface microstructure is achieved, and optical encryption materials can be prepared by matching with a photomask.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymer materials, and in particular to a preparation method and application of a double-layer film system material with a self-erasable surface microstructure. Background Art

[0002] Constructing multi-level microstructures on the surface of polymer elastomers can effectively change the optical transmittance and surface wettability of the material. However, the current surface microstructure construction methods mainly rely on spin coating or photolithography. Spin coating has high requirements on the surface roughness and wettability of the substrate material, while photolithography requires high-cost precision processing equipment, which is not conducive to large-scale production.

[0003] In view of this, the present invention has developed a method for constructing a microstructure on the surface of a polymer, which has the advantages of low cost and simple preparation process. In addition, by constructing a microstructure on the surface of a polymer, the optical properties of the material can be regulated, thereby preparing an optical encryption material. Summary of the invention

[0004] The purpose of the present invention is to address the problem of low adhesion caused by the low surface energy of traditional polydimethylsiloxane materials, and the problem of difficulty in large-scale production and high cost due to the complexity of the operating process of constructing a polymer double-layer membrane system using traditional processes. A unique and practical polymer surface microstructure is constructed, which not only has low production cost, but also has a convenient preparation process and is easy to mass produce. It has good application prospects in the field of optical encryption.

[0005] To achieve the above object, on the one hand, the present invention provides a method for preparing a double-layer film system material with a self-erasable surface microstructure, which comprises the following steps:

[0006] S1, using heat-crosslinkable polydimethylsiloxane as a substrate to prepare an elastomer doped with a carbonyl-containing photoinitiator;

[0007] S2, dissolving a polymerizable α-olefin monomer in an organic solvent to obtain a corresponding monomer solution, wherein the chemical structure of the α-olefin monomer is shown in formula (I);

[0008]

[0009] Wherein, R is selected from any one of C1-20 aryl, C1-20 heterocyclic aromatic, C1-20 alkyl, C1-20 acyl, C1-20 ester, C1-20 ketone, C1-20 aldehyde, C1-20 alkoxy, and C1-20 aryloxy;

[0010] S3, using the elastomer of step S1 as a substrate and immersing it in the monomer solution of step S2, using ultraviolet exposure to induce a free radical reaction to generate a surface microstructure on the surface of the elastomer, thereby obtaining a double-layer membrane system material with a self-erasable surface microstructure.

[0011] As a further preferred technical solution of the present invention, the photoinitiator is one of benzophenone, 2,4-dihydroxybenzophenone, Michler's ketone, 2-chlorothioxanthone, isopropylthioxanthone, ethylthioxanthone, butylthioxanthone, and 2,4-diethylthioxanthone.

[0012] As a further preferred technical solution of the present invention, in step S1, the mass proportion of the photoinitiator in the elastomer is 0.1-1%.

[0013] As a further preferred technical solution of the present invention, in step S1, the temperature of cross-linking and curing is 50-60°C.

[0014] As a further preferred technical solution of the present invention, in step S2, the concentration of the prepared monomer solution is 10-20 wt%.

[0015] As a further preferred technical solution of the present invention, in step S2, the α-olefin monomer is acrylamide or 4-hydroxybutyl acrylate.

[0016] As a further preferred technical solution of the present invention, the organic solvent is at least one of methanol, ethanol, acetonitrile, tetrahydrofuran, acetone, cyclopentanone, cyclohexanone, dichloromethane, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, dioxane, hexafluoroisopropanol, cyclopentane, N-methyl-2-pyrrolidone, m-cresol, xylenol, benzene, toluene, xylene, N-vinyl-2-pyrrolidone, butyrolactone, and butyl acetate.

[0017] As a further preferred technical solution of the present invention, in step S3, the power of ultraviolet exposure is 6W, and the exposure time is 1-30min; and / or, the wavelength of ultraviolet light used in ultraviolet exposure is 365nm.

[0018] As a further preferred technical solution of the present invention, in the above-mentioned step S3, a photomask with a preset pattern is used to perform regional exposure on the elastomer immersed in the monomer solution, that is, the exposure light source irradiates the light to the surface of the elastomer through the mask, so that the surface of the elastomer produces a surface microstructure according to the preset pattern, and the pattern is formed by the area where the surface microstructure is produced.

[0019] According to another aspect of the present invention, the present invention also provides an application of a double-layer film system material in patterned optical encryption. When the surface of the double-layer film system material is dried, the pattern disappears; when the surface of the double-layer film system material is soaked with water, the pattern reappears.

[0020] The present invention soaks the elastomer in a monomer solution, and the initiator doped in the elastomer is converted into free radicals after absorbing UV light, and begins to attack the double bonds in the monomer, so that the monomer and the surface of the elastomer are grafted through covalent bonding, thereby generating a surface microstructure in the grafting area. After the reaction is completed, the obtained double-layer membrane system is exposed to the air, so that the system loses water molecules and the surface microstructure undergoes a self-erasing phenomenon; after the double-layer system is soaked with deionized water (or its type aqueous solution), the system absorbs water again and the surface microstructure reappears.

[0021] Compared with the prior art, the present invention can achieve the following beneficial effects:

[0022] 1) The present invention only requires that the monomer solution infiltrate the elastomer and initiate a free radical reaction through UV exposure to achieve the construction of a double-layer membrane system. The preparation process is simple and convenient, can be promoted on a large scale, and has excellent feasibility.

[0023] 2) The double-layer membrane system in the present invention has a surface microstructure, which can change the optical transmittance and surface energy of the elastomer, improve the adhesion of the elastomer surface, and provide a wider range of practical applications for PDMS, an elastic material with excellent biocompatibility and environmental safety.

[0024] 3) The surface of the elastomer obtained by the photochemical reaction of the present invention will form some unique and practical surface microstructures, which not only overcomes the defects of traditional processing methods, realizes the rapid construction of polymer surface microstructures, but also can prepare optical encryption materials in conjunction with photomasks. In addition, compared with commercially available PDMS elastomers, the surface microstructure produced by the double-layer membrane system has excellent uniqueness and practicality, and its optical behavior is easy to achieve. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0026] Figure 1 This is a physical picture of the elastic substrate of Example 1.

[0027] Figure 2 The surface microstructure formed by using acrylamide as the grafting monomer in Example 1 is shown under an optical microscope.

[0028] Figure 3 This is the surface contact angle test result of the elastomer without the grafted monomer in Example 1.

[0029] Figure 4 The contact angle test result of the elastomer surface in Example 1 in which the grafted monomer is acrylamide.

[0030] Figure 5 The surface microstructure formed by using 4-hydroxybutyl acrylate as the grafting monomer in Example 2 under an optical microscope

[0031] Figure 6 The contact angle test result of the elastomer surface in Example 2 in which the grafted monomer is 4-hydroxybutyl acrylate.

[0032] Figure 7 It is a transmittance test curve diagram of the double-layer membrane system material in Examples 1 and 2.

[0033] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0034] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0035] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0036] Example 1

[0037] The preparation method of the double-layer film system material with a self-erasable surface microstructure provided in this embodiment is carried out according to the following steps:

[0038] S1. Synthesis of elastic substrate:

[0039] 9.61 g of component A (ethylbenzene) of DC184 and 2.88 g of component B (2,4,6,8-tetravinyl-2,4,6,8-tetramethylcyclotetrasiloxane) were mixed with 0.0978 g of benzophenone dissolved in 1 ml of toluene, stirred evenly, and placed in a centrifuge for degassing. The mixture was then poured into a 12.5 cm × 12.5 cm square container, placed in an oven, and cross-linked and cured at 60°C to obtain an elastomer doped with benzophenone (such as Figure 1 shown).

[0040] S2. Preparation of monomer solution:

[0041] 3 g of acrylamide was dissolved in 12 ml of deionized water to obtain a 20 wt % acrylamide monomer solution.

[0042] S3. Microstructure formation:

[0043] The elastomer is placed in a suitable container, and an acrylamide monomer solution is poured in so that it completely covers the surface of the elastomer. Subsequently, the free radical reaction is initiated by a UV exposure machine under the conditions of 365nm, 3V, and 2A, and the exposure time is 10min. After exposure, a surface microstructure of a certain area (exposure position) is generated on the surface of the elastomer, and a double-layer membrane system material is finally obtained. The double-layer membrane system material is taken out from the acrylamide monomer solution. After being separated from the aqueous solution, as the water on the surface of the elastomer evaporates, it can be seen that the microstructure gradually disappears until it disappears completely; after the double-layer membrane system material whose surface microstructure has disappeared is soaked with water, it is found that the microstructure reappears; when the surface is dried again, the microstructure disappears again, and this can be repeated to achieve repeated disappearance / appearance of the microstructure.

[0044] When the surface of the double-layer membrane system material prepared in Example 1 is fully wetted, densely distributed wrinkles can be seen by observing its surface through an optical microscope. Figure 2 As shown, it shows that the double-layer membrane system of the present invention can successfully construct a surface microstructure using acrylamide as a grafting monomer.

[0045] The surface contact angle test was performed on the elastomer without grafted acrylamide monomer in Example 1 (referring to the elastomer doped with benzophenone in step S1) and the elastomer with grafted acrylamide monomer (referring to the double-layer membrane system material finally obtained in step S3). The results are as follows: Figure 3 and 4 As shown, by comparison, after grafting acrylamide monomer, the surface of the elastomer increases, which is beneficial to the construction of surface microstructure.

[0046] Example 2

[0047] The preparation method of the double-layer film system material with a self-erasable surface microstructure provided in this embodiment is carried out according to the following steps:

[0048] S1. Synthesis of elastic substrate:

[0049] Mix 9.61 g of DC184 component A (ethylbenzene) and 2.88 g of component B (2,4,6,8-tetravinyl-2,4,6,8-tetramethylcyclotetrasiloxane) with 0.0978 g of benzophenone dissolved in 1 mL of toluene, stir evenly, put into a centrifuge for degassing, and then pour the mixed solution into a 12.5 cm × 12.5 cm square container, place in an oven, and cross-link and cure at 60°C to obtain an elastomer doped with benzophenone.

[0050] S2. Preparation of monomer solution:

[0051] 3 g of 4-hydroxybutyl acrylate was dissolved in 12 ml of deionized water to obtain a 20 wt % 4-hydroxybutyl acrylate monomer solution.

[0052] S3. Microstructure formation:

[0053] The elastomer is placed in a suitable container, and the 4-hydroxybutyl acrylate monomer solution is poured in to completely cover the surface of the elastomer. Then, the free radical reaction is initiated by using a UV exposure machine under the conditions of 365nm, 3V, and 2A, and the exposure time is 20min. After exposure, a surface microstructure of a certain area (exposure position) is generated on the surface of the elastomer, and finally a double-layer membrane system material is obtained.

[0054] The double-layer membrane system material prepared in step S3 is taken out from the 4-hydroxybutyl acrylate monomer solution. After being separated from the aqueous solution, as the water on the surface of the elastomer evaporates, the visible surface microstructure gradually disappears until it disappears, thereby achieving self-erasing. After the surface of the double-layer membrane system material whose surface microstructure has disappeared is soaked with water, the visible microstructure reappears. When the surface is dried again, the microstructure disappears again. By repeating this process, the microstructure can be repeatedly hidden / reappeared.

[0055] When the surface of the double-layer membrane system material prepared in Example 2 is fully wetted, the surface is observed through an optical microscope, and dense wrinkles are observed on the surface. Figure 5 As shown, it shows that the double-layer membrane system of the present invention successfully constructs the surface microstructure by using 4-hydroxybutyl acrylate as the grafting monomer.

[0056] The surface contact angle test was performed on the elastomer without 4-hydroxybutyl acrylate monomer grafted and the elastomer with 4-hydroxybutyl acrylate monomer grafted in Example 2. The results are as follows: Figure 6 . By comparison, it can be seen that after grafting 4-hydroxybutyl acrylate monomer, the surface of the elastomer increases, which is conducive to constructing the surface microstructure. Further, the surface contact angles of the elastic grafted 4-hydroxybutyl acrylate monomer prepared in Comparative Example 1 and Example 2 are compared. The surface of the elastomer in Example 2 increases more significantly, and its effect of constructing the surface microstructure is the best.

[0057] The transmittance of the elastomers grafted with different monomers in Examples 1 and 2 and the pure polydimethylsiloxane elastomer was tested. The results are as follows: Figure 7 By comparison, it is found that the transmittance of the polydimethylsiloxane elastomer after the grafted monomer decreases to varying degrees, thereby enabling selective blocking of light radiation and changing important parameters such as the dielectric properties of the material, thereby enabling patterned optical encryption based on the construction of surface microstructures.

[0058] In the process of preparing a double-layer film system material with a self-erasable surface microstructure, the present invention uses a photomask with a preset pattern to perform regional exposure on an elastomer immersed in a monomer solution, that is, local exposure is performed according to the preset pattern, so that the area where the surface microstructure is generated on the surface of the elastomer forms a pattern. The surface of the double-layer film system material after exposure is dried, and the microstructure and pattern disappear; when the surface of the double-layer film system material is soaked with water, the microstructure and pattern reappear. Therefore, based on the constructed microstructure, it can be applied to patterned optical encryption.

[0059] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A method for preparing a double-layer film system material with a self-erasable surface microstructure, characterized in that: The following steps are involved: S1, using heat-crosslinkable polydimethylsiloxane as a substrate to prepare an elastomer doped with a carbonyl-containing photoinitiator; S2, dissolving a polymerizable α-olefin monomer in an organic solvent to obtain a corresponding monomer solution, wherein the chemical structure of the α-olefin monomer is shown in formula (I); Wherein, R is selected from any one of C1-20 aryl, C1-20 heterocyclic aromatic, C1-20 alkyl, C1-20 acyl, C1-20 ester, C1-20 ketone, C1-20 aldehyde, C1-20 alkoxy, and C1-20 aryloxy; S3, using the elastomer of step S1 as a substrate and immersing it in the monomer solution of step S2, using ultraviolet exposure to induce a free radical reaction to generate a surface microstructure on the surface of the elastomer, thereby obtaining a double-layer membrane system material with a self-erasable surface microstructure.

2. The method for preparing a double-layer film system material with a self-erasable surface microstructure according to claim 1, characterized in that: The photoinitiator is one of benzophenone, 2,4-dihydroxybenzophenone, Michler's ketone, 2-chlorothioxanthone, isopropylthioxanthone, ethylthioxanthone, butylthioxanthone and 2,4-diethylthioxanthone.

3. The method for preparing a double-layer film system material with a self-erasable surface microstructure according to claim 1, characterized in that: The mass proportion of the photoinitiator in the elastomer is 0.1-1%.

4. The method for preparing a double-layer film system material with a self-erasable surface microstructure according to claim 1, characterized in that: In step S1, the temperature of cross-linking and curing is 50-60°C.

5. The method for preparing a double-layer film system material with a self-erasable surface microstructure according to claim 1, characterized in that: In step S2, the concentration of the prepared monomer solution is 10-20 wt%.

6. The method for preparing a double-layer film system material with a self-erasable surface microstructure according to claim 1, characterized in that: In step S2, the α-olefin monomer is acrylamide or 4-hydroxybutyl acrylate.

7. The method for preparing a double-layer film system material with a self-erasable surface microstructure according to claim 1, characterized in that: The organic solvent is at least one of methanol, ethanol, acetonitrile, tetrahydrofuran, acetone, cyclopentanone, cyclohexanone, dichloromethane, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, dioxane, hexafluoroisopropanol, cyclopentane, N-methyl-2-pyrrolidone, m-cresol, xylenol, benzene, toluene, xylene, N-vinyl-2-pyrrolidone, butyrolactone, and butyl acetate.

8. The method for preparing a double-layer film system material with a self-erasable surface microstructure according to claim 1, characterized in that: In step S3, the power of ultraviolet exposure is 6W, and the exposure time is 1-30min; and / or the wavelength of ultraviolet light used in ultraviolet exposure is 365nm.

9. The method for preparing a double-layer film system material with a self-erasable surface microstructure according to any one of claims 1 to 8, characterized in that: In step S3, a photomask having a preset pattern is used to perform regional exposure on the elastomer immersed in the monomer solution, so that the region with the surface microstructure generated on the surface of the elastomer forms a pattern.

10. An application of a double-layer film system material prepared by the preparation method according to claim 9 in patterned optical encryption, characterized in that: When the surface of the double-layer film system material is dried, the pattern disappears; when the surface of the double-layer film system material is soaked with water, the pattern reappears.